World Bank Group Global Market Survey : Digital Technology and the Future of Finance - World Bank; International Finance Corporation (World Bank, Washington, DC, 2022)
This report documents the main findings of the Word Bank Group Survey on Digital Transformation and the Future of Finance. The survey was conducted between May 2020 and January 2021 and focused on the digital transformation of financial services and its impact on financial markets and regulatory environments across the world. The survey covered a wide range of market participants, with a focus on those from Emerging Market and Developing Economies (EMDEs). This survey of market participants complemented earlier surveys of the official sector by the World Bank Group, IMF, and Cambridge Center for Alternative Finance. As a follow-up to the IMF-WBG Bali Fintech Agenda, 3 the IMF and the WBG undertook a global fintech survey (GFS 2019) of central banks, finance ministries, and regulatory agencies, which underpinned the stock-taking paper ‘Fintech: The Experience So Far’ published by the IMF and the World Bank in 2019. GFS 2019 collected insights from 96 official-sector respondents worldwide related to fintech developments in their respective jurisdictions. It found that the official sector broadly expected fintech to increase competition, particularly in payments, and to further financial inclusion for both households and MSMEs. The results suggested the need to modify regulatory approaches and legal frameworks. The WBG-CCAF survey of regulators from 111 jurisdictions on alternative finance (WBG-CCAF 2019) corroborated regulators’ support for technology-driven finance and their plans to further develop regulatory frameworks covering P2P, equity crowdfunding, and initial coin offerings. Purpose-built regulations for these new sectors often impose more obligations than existing regulations. The CCAF-WB 2020 Global COVID-19 FinTech Regulatory Rapid Assessment Study reported regulators’ observations that due to accelerated adoption of fintech products and services during the pandemic, particularly in emerging markets, fintech regulation was a priority, along with concerns about rising cybersecurity, operational, and consumer protection risks. This survey largely confirmed the observations of regulators and market participants from previous surveys, reinforcing the competition and inclusion aspects of fintech and the need to continue to address emerging risks, adapt regulatory frameworks, and reduce barriers to innovation.